2018
DOI: 10.1136/jmedgenet-2017-104999
|View full text |Cite
|
Sign up to set email alerts
|

FAM46Amutations are responsible for autosomal recessive osteogenesis imperfecta

Abstract: We conclude that mutations are responsible for a severe form of OI with congenital bowing of the lower limbs and suggest screening this gene in unexplained OI forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
(16 reference statements)
1
36
0
1
Order By: Relevance
“…Indeed, all 19 genes known to cause osteogenesis imperfecta (OI) [58][59][60] were actively expressed 1 1 in osteocytes and 14 were present in the osteocyte transcriptome signature (Fig. 6c).…”
Section: Osteocyte Transcriptome Signature Genes Are Associated With mentioning
confidence: 99%
“…Indeed, all 19 genes known to cause osteogenesis imperfecta (OI) [58][59][60] were actively expressed 1 1 in osteocytes and 14 were present in the osteocyte transcriptome signature (Fig. 6c).…”
Section: Osteocyte Transcriptome Signature Genes Are Associated With mentioning
confidence: 99%
“…Moreover, it has been shown that polymorphism in the second exon of TENT5A may be associated with an increased risk of large-joint osteoarthritis [ 87 ], which is consistent with severe skeletal abnormalities of TENT5A knock-out mice [ 88 ]. Finally, loss-of-function mutations in TENT5A have been reported in patients suffering from severe, autosomal recessive forms of osteogenesis imperfecta [ 89 ].…”
Section: Ncpaps and Adenylationmentioning
confidence: 99%
“…Recently, mutations in the gene TENT5A (formerly known as FAM46A), encoding the terminal nucleotidyltransferase 5A were described as disease-causing in three patients. These patients are moderately to severely affected [20]. The expression of TENT5A in osteoblasts suggests a role in bone homeostasis and a previously unknown function of this enzyme in mineralized tissue was described.…”
Section: Tent5amentioning
confidence: 90%